Directory of world cinema - Palmer, Tim (Directory of world cinema, 2013)
Artistic, intellectual, and appreciably avant-garde, the French film industry has, perhaps more than any other national cinema, been perennially at the centre of international filmmaking. With its vigorous business and wide-ranging film culture, France has also been home historically to some of the most influential filmmakers and movements - and, indeed, the very first motion picture was screened in Paris in 1895.